2012
DOI: 10.1007/s00586-012-2594-3
|View full text |Cite
|
Sign up to set email alerts
|

Footprint mismatch in total cervical disc arthroplasty

Abstract: Purpose Cervical disc arthroplasty has become a commonplace surgery for the treatment of cervical radiculopathy and myelopathy. Most manufacturers derive their implant dimensions from early published cadaver studies. Ideal footprint match of the prosthesis is essential for good surgical outcome. Methods We measured the dimensions of cervical vertebrae from computed tomography (CT) scans and to assess the accuracy of match achieved with the most common cervical disc prostheses [Bryan (Medtronic), Prestige LP (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 24 publications
1
40
0
Order By: Relevance
“…Thaler et al reported high rates of undersizing of the most commonly used cervical disc implants, including the PRESTIGE LP, and warned of potential consequences, including subsidence, migration, heterotopic ossification, and biomechanical failure caused by incorrect center of rotation and load distribution. 28 As a general rule, patients tend to return to work when their pain has improved to the point that they are able to work. The patient in this study is asked at each followup after surgery if he/she is employed.…”
Section: Discussionmentioning
confidence: 99%
“…Thaler et al reported high rates of undersizing of the most commonly used cervical disc implants, including the PRESTIGE LP, and warned of potential consequences, including subsidence, migration, heterotopic ossification, and biomechanical failure caused by incorrect center of rotation and load distribution. 28 As a general rule, patients tend to return to work when their pain has improved to the point that they are able to work. The patient in this study is asked at each followup after surgery if he/she is employed.…”
Section: Discussionmentioning
confidence: 99%
“…The design of the available implants is based on anthropometric measurements of the cadavers [ 6 ] and photographs of radiographs [ 7 ]. CT evaluation of bony structures is more accurate, and it has been recently found to be useful in determination of lumbar [ 15 ] and cervical endplates [ 10 ]. Thaler et al [ 10 ] measured the dimensions of cervical vertebrae from computed tomography (CT) scans in 24 patients to assess the accuracy of match achieved with the most common available cervical disc prostheses: Bryan (Medtronic), Prestige-LP (Medtronic), Discover (Depuy), and Prodisc-C (Synthes).…”
Section: Discussionmentioning
confidence: 99%
“…Then the digital measuring tools were used to measure distances after adjusting the axis parallel and perpendicular at each of the endplate on sagittal images, just making sure that there was no obliquity. Four measurements were taken for each endplate as described by Thaler et al [ 10 ]: the AP diameter, the mediolateral diameters at two locations (ML1/2) and the CML diameter as illustrated in Fig. 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative effect of imperfect device positioning and endplate-device matching would likely be amplified in multilevel CDA. 19,20 The incidence of heterotopic ossification (HO) has been found to increase with the number of cervical arthroplasty levels without affecting patient-reported outcomes. 21,22 Further and stronger long-term evidence is still needed in order to evaluate multilevel cervical surgeries.…”
Section: Introductionmentioning
confidence: 99%